Role of Computed Tomography Scan in The Evaluation of Cerebral Palsy in Children - Begum, Momotaj; Yiasmeen, Sabina; Hossain, Mahmud; Ahmed, Shafi; Azad, Salahuddin Al; Jinnat, Mosammat Afroza (KYAMC Journal, 2020)
Background. Cerebral palsy is one of the common childhood neurological problem which occurs due to defect or lesion in immature brain. The worldwide incidence of cerebral palsy is approximately 2-2.5 per 1000 live births. There have been many works on the role of computed tomography scan in the diagnosis of cerebral palsy. Objective: The objective information available from careful review of imaging information such as CT brain scans, is an important adjunct to clinical data. Materials and Methods: This cross sectional study was carried out in the department of Radiology and Imaging, BSMMU and department of Paediatric Neurology unit over a period of 12 months from January 2019 to December 2019. We calculated the sensitivity, specificity, positive predictive value, negative predictive value and accuracy of CT scan in diagnosis of CP in children. Results: This cross sectional study was carried out on consecutively selected 94 children below 15 years having clinical evidence of cerebral palsy. Among the study subjects 86.2% were diagnosed as cerebral palsy through CT scan. Conclusion: The sensitivity and specificity of CT scan of present study was found to be quite high in children which suggests a CT scan as an effective investigation for the diagnosis of cerebral palsy. KYAMC Journal Vol. 11, No.-1, April 2020, Page 3-8